A new funnel framework to support innovation management in SMEs - Stefano Biazzo; Patrizia Garengo; Giovanni Bernardi (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
The effective management of an innovation process is widely recognized as an important pre-requisite for organisations competing in the current business environment, irrespective of size. Although front-end activities have now long been recognized as crucial for successful new product development, many companies, especially small and medium enterprises, appear unaware of the importance of these activities. This study aims to identify a structured approach for supporting the assessment and improvement of innovation management processes in SMEs. A framework, inspired by the funnel of innovation, is designed and described in detail in all its phases, and a methodology for its implementation is suggested.
Keywords: 650; Innovation management; small and medium enterprises; new product development; innovative organisation